Death as a factor in the dissolution of the marriage - DULLAK, KAZIMIERZ (Prawo Kanoniczne, 2019)
The purpose of this submission is to indicate the consequences resulting from the death of a previously married person. What does death do to the marriage itself and to the spouse in both civil and ecclesiastical law? Before doing so, however, it will be necessary to define what the phenomenon of death itself is from both a medical and a legal point of view.